2022
DOI: 10.3389/fsysb.2022.1044281
|View full text |Cite
|
Sign up to set email alerts
|

Teaching computational systems biology with an eye on quantitative systems pharmacology at the undergraduate level: Why do it, who would take it, and what should we teach?

Abstract: Computational systems biology (CSB) is a field that emerged primarily as the product of research activities. As such, it grew in several directions in a distributed and uncoordinated manner making the area appealing and fascinating. The idea of not having to follow a specific path but instead creating one fueled innovation. As the field matured, several interdisciplinary graduate programs emerged attempting to educate future generations of computational systems biologists. These educational initiatives coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Intriguingly, computational systems biology has developed over the past two decades in a somewhat uncoordinated fashion, driven by research into a smorgasbord of topics. This almost uninhibited opportunity to advance in novel areas made the field very attractive (Androulakis, 2022). Beyond the application of systems biology to challenging problems in biology, medicine, agriculture, environmental stewardship and other areas of great societal importance, the goals of computational systems biology fall into three very broad categories, the first two of which, intriguingly, point in opposite directions.…”
Section: Research Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, computational systems biology has developed over the past two decades in a somewhat uncoordinated fashion, driven by research into a smorgasbord of topics. This almost uninhibited opportunity to advance in novel areas made the field very attractive (Androulakis, 2022). Beyond the application of systems biology to challenging problems in biology, medicine, agriculture, environmental stewardship and other areas of great societal importance, the goals of computational systems biology fall into three very broad categories, the first two of which, intriguingly, point in opposite directions.…”
Section: Research Goalsmentioning
confidence: 99%
“…Because systems biology is applicable to numerous problem spaces, it offers the opportunity to custom tailor a course to a specific topic or home department. Examples include a course dedicated to analyzing the systemic nature of a specific disease of interest (Voit et al, 2012) and a systems biology course with emphasis on quantitative systems pharmacology (Androulakis, 2022).…”
Section: Educationmentioning
confidence: 99%
“…A 2018 industry-wide survey of pharmaceutical companies revealed that fewer than one in 10 QSP team members identified as biologists; most QSP modelers have backgrounds in Pharmaceutical Sciences, Engineering, and Computational Biology/Bioinformatics ( Nijsen et al, 2018 ). Job descriptions and education requirements for QSP modelers often require software development skills and training in clinical pharmacology, pharmacokinetics, or applied mathematics but require little or no biological sciences background ( Androulakis, 2022 ; Zhang et al, 2022b ; Gallo, 2022 ). In our capacity as consultants interacting with modeling groups in pharmaceutical companies, we have observed that it is exceedingly rare for life scientists to be core members of modeling teams despite some recommendations ( Leil and Bertz, 2014 ; Aghamiri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%